2003
DOI: 10.1046/j.1540-8191.2003.02002.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of Minimally Invasive and Standard Techniques for Aortic Valve Replacement: Initial Experience in the First Hundred Patients

Abstract: Our data demonstrate that a partial upper sternotomy is a safe and effective technique for AVR. Postoperative morbidity is not significantly reduced in patients undergoing AVR by this approach. Further studies in a larger patient population are necessary to assess whether postoperative morbidity is significantly reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 18 publications
2
29
2
1
Order By: Relevance
“…In our series, the minimally invasive access group demonstrated CPB and aortic clamping times, respectively: 142.7 ± 59.5 min and 88.6 ± 31.5 min. These data were comparable to those presented by Plass et al [35] in an article published about the subject in 2009, were longer than those with median sternotomy, but similar in relation to morbimortality [42,43].…”
Section: Discussionsupporting
confidence: 87%
“…In our series, the minimally invasive access group demonstrated CPB and aortic clamping times, respectively: 142.7 ± 59.5 min and 88.6 ± 31.5 min. These data were comparable to those presented by Plass et al [35] in an article published about the subject in 2009, were longer than those with median sternotomy, but similar in relation to morbimortality [42,43].…”
Section: Discussionsupporting
confidence: 87%
“…Many studies have shown that it can be done safely with mortality and morbidity similar to conventional full sternotomy aortic valve surgery [3][4][5][6][7][8][9][10][11][12][13][14][15]. Several studies have also shown that the minimal access approach contributes to better surgical outcomes compared to a full sternotomy [3][4][5][14][15][16] although it is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, operative times (duration of aortic cross-clamp and cardiopulmonary bypass [CPB]) are significantly longer [2,7,8] That has limited the diffusion of MIAVR during the last decade. The recent introduction in clinical practice of the aortic sutureless bioprostheses may simplify and shorten operative times in MIAVR, thus influencing the riskbenefit balance between standard sternotomy and ministernotomy (MS) or MT.…”
mentioning
confidence: 99%